2005
DOI: 10.1016/j.trstmh.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis as a predictor of childhood malnutrition in Orang Asli children in Malaysia

Abstract: A cross-sectional study to examine the association of giardiasis with protein-energy malnutrition, vitamin A deficiency and iron deficiency anaemia was conducted among Orang Asli children in Selangor, Malaysia. A total of 281 children aged 2-15 years were studied. The data were collected using structured questionnaires, anthropometric measurements and laboratory analysis of blood and faecal samples. The results showed that 24.9% of the children were infected with Giardia duodenalis, while 56.5, 61.3 and 15.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 11 publications
7
57
0
1
Order By: Relevance
“…This could indicate that infection transmission occurs during intermediate childhood, perhaps when children normally play in very close contact. This result was in agreement with a study of a rural community in Malaysia, which reported higher association among two to six year-old children 3 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This could indicate that infection transmission occurs during intermediate childhood, perhaps when children normally play in very close contact. This result was in agreement with a study of a rural community in Malaysia, which reported higher association among two to six year-old children 3 .…”
Section: Discussionsupporting
confidence: 93%
“…However, it is common for acute symptomatic individuals to present with diarrhea or clinical manifestations of malabsorption. Malabsorption of fat, D-xylose, vitamin A and vitamin B12 have been reported associated with this infection 3,12,34,47 . Chronic giardiasis in children is generally associated with clinical manifestations of failure to thrive 1,9,48,53 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies among Aboriginal children in Selangor, Malaysia, reported a higher prevalence of low serum retinol concentration and significant wasting among children infected with G. duodealis than in uninfected children. 16,33 Similarly, previous studies from Thailand and Mexico found that Giardia -infected children were more likely to be vitamin A-deficient and had lower concentrations of serum retinol than Giardia -free children. 31,32 Furthermore, a case of VAD phrynoderma (a rare form of follicular hyperkeratosis associated with deficiencies in vitamins A or C or essential fatty acids) has been reported to be associated with chronic giardiasis in a six-year-old boy in France.…”
mentioning
confidence: 79%
“…Supporting the notion that there is an impact on developmental delay, early childhood giardiasis is associated with persistent diarrhea (5), which is a major risk factor for childhood stunting (height-for-age Z score [HAZ] of less than -2) (6). While in some studies stool carriage of G. lamblia is a strong predictor of either wasting or stunting (7)(8)(9), other studies of equal validity demonstrate no association between giardiasis and childhood growth (10). While Goto et.…”
Section: Introductionmentioning
confidence: 99%